Detection and metabolic investigations of a novel designer steroid: 3‐chloro‐17α‐methyl‐5α‐androstan‐17β‐ol. Issue 7 (23rd June 2015) - Cawley, Adam T.; Blakey, Karen; Waller, Christopher C.; McLeod, Malcolm D.; Boyd, Sue; Heather, Alison; McGrath, Kristine C.; Handelsman, David J.; Willis, Anthony C.
Abstract : In 2012, seized capsules containing white powder were analyzed to show the presence of unknown steroid‐related compounds. Subsequent gas chromatography–mass spectrometry (GC‐MS) and nuclear magnetic resonance (NMR) investigations identified a mixture of 3α‐ and 3β‐ isomers of the novel compound; 3‐chloro‐17α‐methyl‐5α‐androstan‐17β‐ol. Synthesis of authentic reference materials followed by comparison of NMR, GC‐MS and gas chromatography‐tandem mass spectrometry (GC‐MS/MS) data confirmed the finding of a new 'designer' steroid. Furthermore, in vitro androgen bioassays showed potent activity highlighting the potential for doping using this steroid. Due to the potential toxicity of the halogenated steroid, in vitro metabolic investigations of 3α‐chloro‐17α‐methyl‐5α‐androstan‐17β‐ol using equine and human S9 liver fractions were performed. For equine, GC‐MS/MS analysis identified the diagnostic 3α‐chloro‐17α‐methyl‐5α‐androstane‐16α, 17β‐diol metabolite. For human, the 17α‐methyl‐5α‐androstane‐3α, 17β‐diol metabolite was found. Results from these studies were used to verify the ability of GC‐MS/MS precursor‐ion scanning techniques to support untargeted detection strategies for designer steroids in anti‐doping analyses. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Analysis of seized capsules identified a mixture of 3α‐ and 3β‐ isomers of the novel compound; 3‐chloro‐17α‐methyl‐5α‐androstan‐17β‐ol. Synthesis of authentic reference materials, in vitro androgen bioassays and in vitro metabolic investigations were performed to confirm the diagnostic 3α‐chloro‐17α‐methyl‐5α‐androstane‐16α, 17β‐diol metabolite for equine testing and generic 17α‐methyl‐5α‐androstane‐3α, 17β‐diol metabolite for human testing. Results from these studies were used to propose a workflow for designer steroid investigations in anti‐doping laboratories.